Urban and Periurban Forest Diversity and Ecosystem Service - Justin Morgenroth (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Recent special issues in various journals have focused on "urban ecosystem services". There is also an increasing amount of studies on "urban ecology", "urban tree management", "arboriculture", "urban biodiversity", and "ecosystem services" from wildland forests. This Special Issue aims to fill a void and focus on the socio-ecological diversity and the economic value of the ecosystem services from urban and peri-urban forests. Urban and peri-urban forests are tree dominated ecosystems in and near human settlements, while ecosystem services are the direct economic, social, and environmental benefits provided by their structural components and ecological functions.